1998
DOI: 10.1046/j.1523-5378.1998.08041.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Omeprazole‐Amoxicillin‐Clarithromycin (OAC) Therapy for Helicobacter pylori Infection in a Japanese Population

Abstract: Two weeks PPI/AC therapy is highly effective for cure of H. pylori infection in the Japanese population. The low dose one month regimen and the one week OAC regimen were also effective in our patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…They have provided cure rates as high as 80% to 90% with few adverse effects. [1][2][3][4] However, the number of patients with treatment failure has begun to increase with the increased levels of treatment for this bacterium. Therefore, it is urgently necessary to establish a standard re-treatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…They have provided cure rates as high as 80% to 90% with few adverse effects. [1][2][3][4] However, the number of patients with treatment failure has begun to increase with the increased levels of treatment for this bacterium. Therefore, it is urgently necessary to establish a standard re-treatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a multi-center study performed in France demonstrated a somewhat higher, although not significant, eradication rate with lowdose clarithromycin triple therapy compared with the conventional regimen [17] . In a study by Miwa H et al [15] using different doses of omeprazole-clarithromycin-amoxicillin, in their low-dose group of omeprazole 20 mg, amoxicillin 750 mg and clarithromycin 200 mg all b.i.d, the eradication rates by ITT and PP were 82.5% and 90% respectively. In our study, the eradication rate of low-dose regimen was 85% and 88% by ITT and PP analysis, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The treatments were well tolerated and associated with a high compliance rate. Many studies have compared different doses of clarithromycin in H pylori eradication, with contradictory results, but those that have evaluated clarithromycinamoxicillin combination in low-dose regimens for H pylori eradication are scarce [15] . Hp consensus groups have generally recommended a 500 mg b.i.d dosage of clarithromycin for H pylori eradication [7,8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] This treatment regimen is known to be effective for eradication in 80-90% of cases, with few adverse effects. [9][10][11] However, there have been few reports about the efficacy and safety of eradication therapy for H. pylori in hemodialysis patients. [12,13] CAM is metabolized both in the liver and kidney, [14] while AMOX is metabolized mainly in the kidney.…”
Section: Introductionmentioning
confidence: 99%